The Immune Landscape of Human Primary Lung Tumors Is Th2 Skewed - Frafjord, Astri; Buer, Linn; Hammarström, Clara; Aamodt, Henrik; Woldbæk, Per Reidar; Brustugun, Odd Terje; Helland, Åslaug; Øynebråten, Inger; Corthay, Alexandre (Frontiers in Immunology, 2021)
Tumor-specific T helper (Th) cells have a central role in the immune response against cancer. However, there exist distinct Th cell subsets with very different and antagonizing properties. Some Th subsets such as Th1 protect against cancer, while others (Th2, T regulatory/Treg) are considered detrimental or of unknown significance (T follicular helper/Tfh, Th17). The Th composition of human solid tumors remains poorly characterized. Therefore, we established a four-color multiplex chromogenic immunohistochemical assay for detection of Th1, Th2, Th17, Tfh and Treg cells in human tumor sections. The method was used to analyze resected primary lung tumors from 11 patients with non-small cell lung cancer (NSCLC). Four microanatomical regions were investigated: tumor epithelium, tumor stroma, peritumoral tertiary lymphoid structures (TLS) and non-cancerous distal lung tissue. In tumor epithelium and stroma, most CD4+ T cells identified had either a Th2 (GATA-3+CD3+CD8-) or Treg (FOXP3+CD3+CD8-) phenotype, whereas only low numbers of Th1, Th17, and Tfh cells were observed. Similarly, Th2 was the most abundant Th subset in TLS, followed by Treg cells. In sharp contrast, Th1 was the most frequently detected Th subset in non-cancerous lung tissue from the same patients. A higher Th1:Th2 ratio in tumor stroma was found to be associated with increased numbers of intratumoral CD8+ T cells. The predominance of Th2 and Treg cells in both tumor stroma and tumor epithelium was consistent for all the 11 patients investigated. We conclude that human primary NSCLC tumors are Th2-skewed and contain numerous Treg cells. If human tumors are Th2-skewed, as our data in NSCLC suggest, reprogramming the type of immune response from a detrimental Th2 to a beneficial Th1 may be critical to increase the response rate of immunotherapy.